ENTEROPATHOGENIC ESCHERICHIA COLI (EPEC) ISOLATED FROM PSITTACINE BIRDS (Fiep Bulletin - online, 2011)
Fecal swabs were collected from 80 psittacine birds, analyzed for the presence of Escherichia coli andinvestigated for the genes encoding the attaching and effacing (eae) and enteropathogenic E. coli EAF plasmid (EAF). The results showed that two of 24 E. coli isolates, belonged to serogroups O76 and O128, were eae positive. All strains were negative for gene encoding for EAF. Our findings showed that some E. coli isolated from psittacine birds present the same virulence factors as human enteropathogenic E. coli and suggest that amazon parrots constitute a reservoir of atypical EPEC.
Keywords: Psittacine birds; APEC; Zoonosis